2017
DOI: 10.25073/2525-2445/vnufs.4155
|View full text |Cite
|
Sign up to set email alerts
|

The Vietnamese Agenda of Adopting English as a Medium of Instruction

Abstract: English as a medium of instruction has been recently adopted in Vietnam's educational system. This gives rise to a concern as why a Vietnamese-speaking country decided to endorse EMI programs as one of its critical educational reforms. This paper aims to analyse the literature to explore the various agendas (social, economic, political, and educational) that underlie the EMI expansion. It examines the world literature as a framework of reference for analysing the Vietnamese case. Hopefully, the paper will prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The unitary theory of language use, on the other hand, maintains that speakers possess only a single grammar, or language system. The features that speakers choose to speak are governed by the speaker's sociolingual competence about the unique communica ve context rather than the grammar of a specific language [16][17][18][19]. This indicates that the bilingual or mul lingual person employs a single internal system that accesses all learned language, not that there are two or more dis nct language systems.…”
Section: Dis Nc Ons Between Translanguaging and The Tradi Onal Use Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…The unitary theory of language use, on the other hand, maintains that speakers possess only a single grammar, or language system. The features that speakers choose to speak are governed by the speaker's sociolingual competence about the unique communica ve context rather than the grammar of a specific language [16][17][18][19]. This indicates that the bilingual or mul lingual person employs a single internal system that accesses all learned language, not that there are two or more dis nct language systems.…”
Section: Dis Nc Ons Between Translanguaging and The Tradi Onal Use Of...mentioning
confidence: 99%
“…This may become a big problem in English classes where communica on is the goal because the excessive use of L1 hinders students from acquiring the target language due to the reduced exposure me. Overusing translanguaging also makes students feel that they can switch to speaking L1 whenever they find expressing their ideas in L2 difficult [17]. Students may lose mo va on to improve their English skills, resul ng in low proficiency levels.…”
Section: Using Translanguaging In Higher Education In the Vietnamese ...mentioning
confidence: 99%
“…According to Nha (2017), one of the reasons that EMI courses are not effective enough is lacking suitable teaching methods [3]. Although some Asian countries have stipulated conducting CLT in English class as an educational policy, CLT is still not that successful in Asian English classrooms because of a series of contextual elements [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research has shown that EMI environment could motivate students and enhance both their academic competency and English proficiency if English is properly utilized [2]. Nha (2017) stressed that appropriate teaching methodology is essential for implementing EMI courses successfully [3]. However, although development of English education has been seen in Asia, there has not been a breakout in English teaching approach in Asian context [4].…”
Section: Introductionmentioning
confidence: 99%
“…Interview findings showed several challenges as previous studies have documented: 1) a lack of lecturers' language abilities, 2) a lack of students' language abilities, 3) a lack of effective teaching methods, and 4) a lack of resources. In this regard, it must be suggested that the implementation of teaching methodologies and EMI are not holistic but could be context specific (Nha, 2017). Therefore, the context and culture of the students need to be considered when evaluating EMI and the teaching methodologies used within a particular context.…”
Section: Emi Research In Asiamentioning
confidence: 99%